The future of mobility and its impact on the automobile insurance industry. Issue 1 (10th March 2020) - Gatzert, Nadine; Osterrieder, Katrin
Abstract: Among the trends impacting most industries are new mobility concepts, digitalization, urbanization, rising environmental awareness, and demographic change. The automobile insurance industry, in particular, is strongly affected by new mobility concepts, including autonomous, shared, and electric vehicles, which are expected to increasingly impact the risk exposure and insurance demand in the future. Identifying and assessing the resulting risk and opportunity landscape from these trends thus becomes a major strategic challenge for insurers. The aim of this paper is to analyze the trends that impact the field of mobility and thus automobile insurers. Based on this, we derive a set of strategic response measures for insurers to enable them to be prepared for the future of mobility.